2005
DOI: 10.1083/jcb.200407078
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural identification of uncoated caveolin-independent early endocytic vehicles

Abstract: Using quantitative light microscopy and a modified immunoelectron microscopic technique, we have characterized the entry pathway of the cholera toxin binding subunit (CTB) in primary embryonic fibroblasts. CTB trafficking to the Golgi complex was identical in caveolin-1null (Cav1−/−) mouse embryonic fibroblasts (MEFs) and wild-type (WT) MEFs. CTB entry in the Cav1−/− MEFs was predominantly clathrin and dynamin independent but relatively cholesterol dependent. Immunoelectron microscopy was used to quantify budd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
463
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(494 citation statements)
references
References 45 publications
23
463
1
2
Order By: Relevance
“…The GEEC pathway has also been suggested to be responsible for the bulk of constitutive fluid phase endocytosis in mammalian cells (Kirkham et al, 2005). Indeed, we found that constitutive fluid-phase endocytosis of HRP was not inhibited in Dyn2 KO cells ( Figure 6A, serum-starved cells).…”
Section: Dyn2 Is Required For Pdgf-stimulated Macropinocytosis But Nsupporting
confidence: 53%
“…The GEEC pathway has also been suggested to be responsible for the bulk of constitutive fluid phase endocytosis in mammalian cells (Kirkham et al, 2005). Indeed, we found that constitutive fluid-phase endocytosis of HRP was not inhibited in Dyn2 KO cells ( Figure 6A, serum-starved cells).…”
Section: Dyn2 Is Required For Pdgf-stimulated Macropinocytosis But Nsupporting
confidence: 53%
“…By contrast, active, selective removal of large rafts by endocytosis and recycling of disassembled, smaller raft units back to the model membrane limited raft size to a nanometer length scale 45 . In this context, it is worth noting that there are well-defined endocytic pathways that selectively internalize lipidraft-associated proteins, and traffic through these pathways is increased after crosslinking the rafts into larger domains 22,46 . Intriguingly, a similar limitation in raft size was achieved by randomly recycling areas of membrane without any selection for large rafts 45 .…”
Section: Limiting L O Domain Sizementioning
confidence: 99%
“…Conversely, a strong leading edge polarization was observed for the CLIC pathway in fibroblasts migrating into a scratch wound [50]. CLICs are the vesicles involved in uptake via the Cdc42 regulated clathrin-independent endocytosis mechanism [53]. This pathway involves the uptake of extracellular fluid and GPI-anchored proteins and requires neither clathrin nor dynamin [53].…”
Section: Excursion 1: Polarization Of the Endocytic Machinery During mentioning
confidence: 99%
“…CLICs are the vesicles involved in uptake via the Cdc42 regulated clathrin-independent endocytosis mechanism [53]. This pathway involves the uptake of extracellular fluid and GPI-anchored proteins and requires neither clathrin nor dynamin [53]. As the CLIC pathway depends on Cdc42 [54] and as Cdc42 itself is polarized to the leading edge, this might explain the strong polarization of the CLIC pathway to this site.…”
Section: Excursion 1: Polarization Of the Endocytic Machinery During mentioning
confidence: 99%